Accelerating Sustainability Competencies in the Younger Generation through the Problem-Based Gamification Learning Model (JURNAL GEOGRAFI, 2026)
Higher education faces the challenge of shaping a young generation that cares about the environment. However, in reality, young people still face difficulties in developing sustainable skills. Problem-Based Game-Based Learning (PBGL) is learning innovation for shaping sustainable competencies. The aims of this study were to determine students' sustainable competencies, determine the effect of length of study on sustainable competencies, and analyse the effect of the PBGL model on sustainable competencies. To analyse the influence of PBGL, a pretest-posttest quasi-experimental design with a control group was used. Meanwhile, to determine the differences in sustainability competencies based on length of study, the Mann-Whitney U test was used. The instrument used was modified from the sustainability competency instrument to suit the characteristics of the research subjects. The results show that sustainability competencies before treatment were at a moderate level. After treatment, the experimental group showed an increase in holistic thinking to 90.5%, followed by an increase in conflict resolution to 95.37%. The experimental group showed a significant increase (t=13.462, p
Keywords: Problem-Based Learning; Gamification Learning; Inovation Learning Model; Sustainability Competencies